Probiotic Lacticaseibacillus rhamnosus GG Increased Longevity and Resistance Against Foodborne Pathogens in Caenorhabditis elegans by Regulating MicroRNA miR-34 - Yun, Bohyun; Ryu, Sangdon; Kang, Minkyoung; Lee, Juyeon; Yoo, Jiseon; Kim, Younghoon; Oh, Sangnam (Frontiers in Cellular and Infection Microbiology, 2022)
In this study, we investigated the relation of probiotic activity of Lacticaseibacillus rhamnosus strain GG (LGG) and expression of microRNA to immune response and longevity in Caenorhabditis elegans host model. First, we evaluated the survival rate of C. elegans due to LGG exposure and bacterial colonization in the intestine. Next, the expression of mRNA and miRNA was analyzed in C. elegans exposure to LGG for 24 h using microarray. After exposure to LGG to C. elegans, colonized LGG was observed in the intestines of C. elegans and induced to extend lifespan. Moreover, persistent LGG in the intestine significantly enhanced the resistance of C. elegans exposed to both pathogenic bacteria and prolonged the lifespan of C. elegans. Transcriptome analysis indicated that LGG affected the expression levels of genes related to the innate immune response and upregulated the abundance of genes in multiple pathways of C. elegans, including Wnt signaling, TGF-beta signaling and mitogen-activated protein kinase (MAPK) pathways. In addition, qRT-PCR analysis confirmed that the expression of antibacterial genes was increased by LGG. Moreover, as the expression of microRNA miR-34 and immune-related pathways increased by exposure to LGG, the lifespan of C. elegans increased. However, in the miR-34 mutant C. elegans, the lifespan by LGG did not increase, so it was determined that miR-34 indirectly affects immune-related pathways. There was no significant difference in the expression of PMK-1 for LGG exposure in miR-34 mutants, suggesting that miR-34 may regulate PMK-1. In conclusion, we suggest that exposure of LGG to C. elegans enhances lifespan and resistance to food-borne pathogen infection by stimulating miR-34 and indirectly promoting PMK-1 activity.